Cannabidiol and SARS-CoV-2 Infection - Vallée, Alexandre (Frontiers in Immunology, 2022)
Cannabidiol (CBD) can prevent the inflammatory response of SARS-CoV-2 spike protein in Caco-2-cells. This action is couple with the inhibition of IL-1beta, IL-6, IL-18 and TNF-alpha, responsible for the inflammatory process during SARS-CoV-2 infection. CBD can act on the different proteins encoded by SARS-CoV-2, and as an antiviral agent to prevent the viral infection. Furthermore, recent studies have shown the possible action of CBD as an antagonist of cytokine release syndromes. In the SARS-CoV-2 pathophysiology, the angiotensin-converting enzyme 2 (ACE2) seems to be the key cell receptor for SARS-CoV-2 infection. The WNT/β-catenin pathway and PPARγ interact in an opposite manner in many diseases, including SARS-CoV-2 infection. CBD exert its activity through the interaction with PPARγ in SARS-CoV-2 infection. Thus, we can hypothesize that CBD may counteract the inflammatory process of SARS-CoV-2 by its interactions with both ACE2 and the interplay between WNT/β-catenin pathway and PPARγ. Vaccines are the only way to prevent COVID-19, but its appears important to find therapeutic complements to treat patients already affected by SARS-CoV-2 infection. The possible role of CBD should be investigated by clinical trials to show its effectiveness.